The influence of antidotal treatment of low-level tabun exposure on cognitive functions in rats using a water maze - Kassa, J; Kunesova, G (Neurotoxicity research, 2006)
In this study, the influence of antidotal treatment of tabun poisoning on cognitive function, in the case of low-level tabun exposure, was studied. The impairment of cognitive function was evaluated by the measurement of spatial learning and memory in rats poisoned with a sublethal dose of tabun and treated with atropine alone or in combination with newly developed oximes {K027 [1-(4-hydroxyiminomethyl- pyridinium)-3-(4-carbamoylpyridinium) propane dibromide] and K048 [1-(4-hydroxyimino- methylpyridinium)-3-(4-carbamoylpyridinium) butane dibromide]} or currently available oxime (trimedoxime), using the Morris water maze. While atropine alone caused an impairment of studied cognitive functions, the addition of an oxime to atropine contributes to the improvement of cognitive performance of treated tabun-poisoned rats regardless of the type of oxime. The differences in the ameliorative effects of oximes on atropine-induced mnemonic deficits were not significant. Therefore, each low-level nerve agent exposure should be treated by complex antidotal treatment consisting of anticholinergic drug and oxime.
Keywords: reakční čas; Behavior, Animal; Male; antidota; Rats, Wistar; lékové interakce; Trimedoxime; Maze Learning; antagonisté muskarinových receptorů; Reaction Time; Oximes; mužské pohlaví; trimedoxim; potkani Wistar; Pyridinium Compounds; krysa rodu Rattus; bludiště - učení; Time Factors; Antidotes; organofosfáty; kognice; atropin; pyridinové sloučeniny; Animals; Drug Interactions; zvířata; Rats; časové faktory; chování zvířat; oximy; Muscarinic Antagonists; Atropine; Organophosphates; Cognition